Abdikarya: Aksi dan karya nyata untuk negeri kita - Praptiningsih, Praptiningsih; Mashuri, Ayunita Ajengtiyas Saputri; Dwiharyadi, Anda; Alfarissi, Fadhil; Arkaan, M. Faturrohman; Aqilla, Hafsah; Humaira, Naffry; Rafli, Muhammad; Syari, Amellya Yunita; Adeliawan, Inaya; Hasan, Najwa Salsabila; Nanda, Rafilah Eka; Anisa, Anisa; Yasmin, Gina Mutiara; Syawalita, Naia (PT WIM Solusi Prima, 2025)
The concept of patriotism (bela negara) as a tangible expression of every citizen’s responsibility in preserving the sovereignty and unity of the nation. National defense is not limited to military action but also includes efforts to overcome non-physical threats such as poverty and ignorance. In this context, community service is recognized as a form of civic duty, exemplified by the ABDIKARYA 2024 program conducted by the Student Executive Board of the Faculty of Economics and Business at UPN